The Effect of Pulse DC and DC Substrate Bias during In Situ Cleaning PVD Process on Surface Roughness - Hashim, Hanizam; Md Nizam, Abd Rahman; Noraiham, Mohamad; Khairul Anuar, Abd Rahman (Elsevier Ltd, 2013)
Surface morphology modification during in situ cleaning of physical vapor deposition (PVD) process is essential to strengthen and prevent unexpected adhesion failure during machining. Applying pulse direct current (PDC) on substrate bias is still uncommon compared to a conventional direct current (DC). This paper is to compare the effects of DC and PDC applied at substrate bias, to the surface roughness and homogeneity. Tungsten carbide (WC) cutting tool insert and argon were used as substrate and inert gas, respectively. The runs were conducted to compare the bias at DC (-500V) and PDC (-200V, -500V, -800V). The surface roughness and homogeneity were inspected using atomic forced microscopy (AFM) and Minitab version 16 exploited to analyze the data. The wettability based on water drop static contact angle on the substrate surface was measured by a digital 800k USB 2.0 CCD DCAM and VIS ver7 (Professional Edition) software. PDC on the substrate bias produced finer grain structures compared to DC. Further increase in PDC voltage resulted in homogenous surface with finer and more globular microstructure with higher surface energy. Hence PDC at optimum level provides better surface readiness prior to coating compared to DC and proven to be a critical factor for further enhancement of coating adhesion.